PUZZLE SABLON EDUKATIF, ARTISTIK, DAN BERBUDAYA - Didik Ari Supriyanto; Gusti Ngurah Kadek Wiranata; Muhammad Faizal; Salsabila Iftinan Ansari; Retno Purwandari (Institut Seni Indonesia Yogyakarta, 2021)
The toy products projected in this entrepreneurship program are toy products that aim to provide an introduction or education to children about the culture and arts in Indonesia which today have begun and are even forgotten by children today. This program is expected that apart from being a forum for entrepreneurship by starting a business, it can be an alternative and solution to maintain and preserve Indonesian culture and arts.